Harnessing the Liquid‐Phase Exfoliation of Graphene Using Aliphatic Compounds: A Supramolecular Approach1. Issue 39 (15th July 2014) - Ciesielski, Artur; Haar, Sébastien; El Gemayel, Mirella; Yang, Huafeng; Clough, Joseph; Melinte, Georgian; Gobbi, Marco; Orgiu, Emanuele; Nardi, Marco V.; Ligorio, Giovanni; Palermo, Vincenzo; Koch, Norbert; et al.
Abstract The technological exploitation of the extraordinary properties of graphene relies on the ability to achieve full control over the production of a high‐quality material and its processing by up‐scalable approaches in order to fabricate large‐area films with single‐layer or a few atomic‐layer thickness, which might be integrated in working devices. A simple method is reported for producing homogenous dispersions of unfunctionalized and non‐oxidized graphene nanosheets in N‐methyl‐2‐pyrrolidone (NMP) by using simple molecular modules, which act as dispersion‐stabilizing compounds during the liquid‐phase exfoliation (LPE) process, leading to an increase in the concentration of graphene in dispersions. The LPE‐processed graphene dispersion was shown to be a conductive ink. This approach opens up new avenues for the technological applications of this graphene ink as low‐cost electrodes and conducting nanocomposite for electronics.